A two stage treatment process for the management of produced ammonium by products in ureolytic bio cementation process. - Mohsenzadeh, A.; Aflaki, E.; Gowthaman, S.; Nakashima, K.; Kawasaki, S.; Ebadi, T. (Springer Nature., 2020)
Since the last decade, microbial-induced carbonate precipitation has been proposed as an environmentally friendly technique to improve the engineering properties of soil. Despite the considerable progress on ureolytic bio-cementation, one of the major concerns that has not been solved yet is related to the production of ammonium. This study aimed to manage ammonium ions to attain a sustainable pathway for bio-cementation treatment. To this end, a two-stage treatment including rinsing of ammonium from soil combined with a recovery of ammonium was considered herein for the first time. In the rinsing process, the followings were studied to optimize ammonium removal from soil: the effects of pH, concentration, and the single salts of the rinse solution. In the subsequent ammonium recovery process, the effects of phosphate source, pH, molar ratio, and Ca2+ ions were extensively investigated. The results revealed that at neutral pH conditions, ammonium removal was the lowest (68.82%). The MgCl2 solution was found to have the greatest ability to remove ammonium followed by CaCl2, NaCl, and distilled water (98.54%, 96.47%, 89.95%, and 74.77%, respectively). The ammonium recovery results showed that 86.8% of ammonium ions could be recovered as a high purity struvite (~ 94%), and that the optimum recovery was achieved at the following conditions: Na2HPO4 as a phosphate source, the Mg2+: NH4+: PO43− molar ratio of 1.2: 1: 1, and a pH of 8.5. Overall, it was demonstrated that the proposed method could be an effective way for sustainable ammonium by-products management.
Keywords: Ammonium by-products.; Desorption.; Environmental management.; Microbial induced carbonate precipitation.; Recovery.